2018
DOI: 10.1051/0004-6361/201833133
|View full text |Cite
|
Sign up to set email alerts
|

LOFAR MSSS: Flattening low-frequency radio continuum spectra of nearby galaxies

Abstract: Aims. The shape of low-frequency radio continuum spectra of normal galaxies is not well understood, the key question being the role of physical processes such as thermal absorption in shaping them. In this work we take advantage of the LOFAR Multifrequency Snapshot Sky Survey (MSSS) to investigate such spectra for a large sample of nearby star-forming galaxies. Methods. Using the measured 150 MHz flux densities from the LOFAR MSSS survey and literature flux densities at various frequencies we have obtained int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 59 publications
(102 reference statements)
5
32
2
Order By: Relevance
“…The observed radio spectral indices are in good agreement with expected values for synchrotron emission. The low-frequency radio spectral index below 1.5 GHz is slightly steeper (with a difference of 2σ) than the value of α = −0.57 ± 0.10 4 found by Chyży et al (2018). Also, we see only a small break in the radio continuum spectrum with ∆α = α low − α high = 0.09 ± 0.05, whereas Chyży et al (2018) found ∆α = 0.18 ± 0.20.…”
Section: Radio Continuum Total Intensity Mapscontrasting
confidence: 67%
See 2 more Smart Citations
“…The observed radio spectral indices are in good agreement with expected values for synchrotron emission. The low-frequency radio spectral index below 1.5 GHz is slightly steeper (with a difference of 2σ) than the value of α = −0.57 ± 0.10 4 found by Chyży et al (2018). Also, we see only a small break in the radio continuum spectrum with ∆α = α low − α high = 0.09 ± 0.05, whereas Chyży et al (2018) found ∆α = 0.18 ± 0.20.…”
Section: Radio Continuum Total Intensity Mapscontrasting
confidence: 67%
“…The low-frequency radio spectral index below 1.5 GHz is slightly steeper (with a difference of 2σ) than the value of α = −0.57 ± 0.10 4 found by Chyży et al (2018). Also, we see only a small break in the radio continuum spectrum with ∆α = α low − α high = 0.09 ± 0.05, whereas Chyży et al (2018) found ∆α = 0.18 ± 0.20. This suggests different CR electron propagation and energy losses in NGC 4013 compared to other spiral galaxies.…”
Section: Radio Continuum Total Intensity Mapscontrasting
confidence: 67%
See 1 more Smart Citation
“…We further adopt typical Milky Way parameters to estimate the energy loss timescales. Regarding the electron spectrum, we assume an −2.0 spectrum up to a few GeV, and −2.4 above that, which is consistent with observed radio spectral index of galaxies (e.g., [11]). Under these assumptions, we obtain MSP 1 ( 9)…”
Section: Pos(icrc2021)1020supporting
confidence: 75%
“…LoLSS data make it possible to detect the turnover from free-free emission with fairly low emission measures, probing low-density (5 cm −3 ) warm ionised gas which may be prevalent in the mid-plane of galaxies (Mezger 1978). Even though one particular statistical study using LOFAR HBA at 144 MHz hinted that free-free absorption plays a minor role (Chyzy et al 2018), the contribution from cooler (T < 1000 K) ionised gas remains largely uncertain (Israel & Mahoney 1990;Emig et al 2020). LoLSS will probe a critical turnover frequency in SED modelling that can characterise ionised gas properties and distinguish its contributions from CRe propagation effects.…”
Section: Galaxiesmentioning
confidence: 99%